2016
DOI: 10.1155/2016/4034129
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Retinopathy and Plasma Glucose and HbA1c: A Validation of Diabetes Diagnostic Criteria in a Chinese Population

Abstract: Aims. This study aimed to evaluate the associations of diabetic retinopathy (DR) with fasting plasma glucose (FPG), 2-hour postload plasma glucose (2hPG), and glycated hemoglobin A1c (HbA1c) in a Chinese population. Materials and Methods. A total of 3124 participants, identified from a population-based survey in Pinggu district, were examined by retinal photography (45°). DR was classified according to the Early Treatment Diabetic Retinopathy Study scale. FPG, 2hPG, and HbA1c were tested and categorized by dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
3
11
2
Order By: Relevance
“…The association between fasting blood glucose and DR is well established. Previous study reported increased prevalence of DR with fasting blood glucose greater than 7.03 mmol/L and for a HbA 1c more than 6.4% (46 mmol/mol) 20 . This further confirms the association between higher fasting blood glucose, triglyceride and DR.…”
Section: Discussionsupporting
confidence: 82%
“…The association between fasting blood glucose and DR is well established. Previous study reported increased prevalence of DR with fasting blood glucose greater than 7.03 mmol/L and for a HbA 1c more than 6.4% (46 mmol/mol) 20 . This further confirms the association between higher fasting blood glucose, triglyceride and DR.…”
Section: Discussionsupporting
confidence: 82%
“…Our study also indicates that higher PBG and HbA1c may contribute to the risk of DR. One study reported that by categorizing PBG and HbA1c by deciles, with the prevalence of DR calculated in each decile, the prevalence of DR increased sharply in the 10th decile, when HbA1c exceeded 6.4%. The threshold of HbA1c for detecting DR is nearly consistent with the criteria for diagnosing diabetes from the World Health Organization [27], meaning that once T2DM is diagnosed, there is already DR complication or a high probability. Another showed that every 1% increase in HbA1c increased the risk of DR by 1.53 times, and every 1 mmol/L increase in PBG increased the risk of DR by 1.07 times [28].…”
Section: Discussionmentioning
confidence: 53%
“…11 Present study showed that the prevalence of retinopathy significantly increased in patients with HbA1c of 7.6% Rui Zhang et al, found that the prevalence of retinopathy increases significantly in the tenth deciles of FPG and HbA1c, with optimal cut off of 7.03mmol/L and 6.4% respectively in Chinese population. 12 All microangiopathies were found in patients with poor glycemic control or high HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%